ANALYSIS OF MAXIMUM RESPIRATORY PRESSURE BEFORE AND AFTER INTERVENTION ACQUATIC PHYSIOTERAPY IN MORBIDLY OBESE BEFORE BARIATRIC SURGERY (Fiep Bulletin - online, 2011)
Introduction: It is known that obesity causes restrictions in lung function due to decreased of diaphragmatic excursion by increased abdominal fat and increase the weigh on the chest wall, leading to a reduction in volume and capacity of lung, this results in a reduced tolerance to effort. Objective: Assess the effects of acquatic physioterapy on maximal respiratory pressures before bariatric surgery. Methodology: The treatment was performed at the Rehabilitation Centre of Assis Gurgacz college - FAG, in the sector of cardiopulmonary physioterapy and in swimming pool. The sample was composed by 3 women aged 18 to 50 years, previously assessed by the gastroenterologist and sent to FAG for physioterapy treatment and released for physical activity in therapeutic pool. Everybody are on the queue to perform bariatric surgery. Results: Before the acquatic treatment, the average MIP by the patients was 80 ± 12 cm/H20 and after was 120 ± 0 cm/H20 with p=0, 058 no significant difference. The MEP has averaged 86,66 ± 12,33 cm/H2O and after was 106,66 ± 5,33 cm/H2O with p=0, 183 no significant difference. Conclusion: This study responded to the research objectives, showing beneficial when used as a means of preparing for the obesity surgery, with increase in maximal respiratory pressures after acquatic physioterapy. It is suggested to repeat the study with a larger sample of individuals.
Keywords: Acquatic Physioterapy; Manovacuometry; Bariatric Surgery